Income distribution policies and economic growth in semiindustrialized countries : a comparative study of Iran, Mexico, Brazil, and South Korea - Looney, Robert E. (New York : Praeger Publishers, 1975)
This book define the appropriate historical or dynamic frame of reference fro examining actual conditions and policies and for designing alternatives approaches.
Includes bibliographical references: p. 182-194.
osa 28/06/2017
Loans
Keywords: Income distribution; Income distribution - Iran; Income distribution - Mexico; Income distribution - Brazil; Income distribution -Korea.